The Origination - Mechanism of the Fundamental - Particles into the Planck's - Confinement - Georgallides, Markos (European Journal of Applied Sciences, 2025)
The Interactions: One of the most important concepts in Geometry is, distance, which is the Quanta in E-geometry, while in Material-Geometry the composition of Opposite, where the Material -Point is the Quanta in Chemistry and Physics. As in Algebra Zero,0, is the Master-key number for all Positive and Negative numbers and this because their sum and multiplication becomes zero, and the same on any coordinate-System where ± axes pass from zero, The Rolling of the Positive ⊕ constituent on the Negative ⊝ constituent, creates the Neutral Material Point which Equilibrium. Angular-Momentum is identical with Spin and consists the First-Discrete-Energy-Monad which occupies, Discrete Value and Direction, in contradiction to the Point which is Nothing, Dimensionless and without any Direction. Quaternion [(+) ↻↺ (-)] ≡ Box which carries the Principal stress σ between Points A (+), B (-) which σ, as Centripetal-acceleration is the minimum Energy becoming from the in-storage AB acceleration and is equal to the Gravity Force g . Because of the Revolving and Periodic acceleration of Gravity g ≡ ± σ exists as the First Energy-Box- , while in the Second Box is followed the Local-Extreme-case where Gravity g ≡ ± σ, and is altered Locally by changing the Principal-stress σ with a Local-uniform-Pressure → ≡ g k = g. [ Force/Area] = G, i.e. The minimum Local - Energy acceleration is the known, Universal Gravitational-constant G = g k = g = σ, such for Macrocosm and for Microcosm, Obeying the Newton`s Laws of motion. This Energy in Hydrogen-Cave as E-M, Conductor ≡ The Pin of Atom → Plug Into their Sockets, which are the Orbit – Bracket–Hooks ≡ The Hands of Atoms ← i.e. The Atoms Plug with their Pins into the other Atoms-Drains = Holes, and so Bond. This Resonance frequency of Hydrogen is Common to all Atoms and to all Compounds in this Cosmos. The Energy-Quaternion , , Monad-Magnitudes exist as DUAL -Nature for Any {⊕, ⊝}, {Position, Motion}, {Universe, Black-Holes}, {Gravity, Antigravity}, Action →. ← Reaction, The Light and others. The STPL- Line Conductors on the [STPL]-Mechanism, are the Physical-Rotors for the Origination of the Cosmic –Particles which transfer Informations as the Signals-Spectrum. From Mechanics-Physics, all Systems Possessing Elasticity ≡ motion and Reaction to the motion, the called mass, are capable of free vibration or vibration ≡ Periodic - motion taking Place in the Absence of External Excitation. This Principle issues for Both Systems Closed The Nucleus or Open Systems The Orbitals. For instance, In order that shifting of an u-d-Quarks from an Anti-Proton into a Proton, the Spin-Pair requires extra input of Energy in (MeV), so that would the Proton Paired with a Neutron and be Stable.